Genetic snd Non-Genetic Effect on Gestation Length and Calf Survival at Weaning in Bali Cattle - Gunawan, A.; Jakaria, Jakaria; Parwoto, Y. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2013)
The aim of this study was to evaluate effect of genetic and non genetic factor on the gestation length (GL) and calf survival to weaning (CS) of Bali cattle. Data were analyzed using Generalized Linier Model (SAS) to observe non-genetic effect. To evaluate the genetic effect, the estimations of heritability were done using Mixed Models analysis with the dam and sire as random effect and parity, year of birth and type of mating as fixed effect in the model besides the residual. The results showed non genetic factors except type of mating influenced the variability of gestation length (GL) and calf survival to weaning (CS) in Bali cattle. The result showed that dam year of birth and parity were found significant source of variation in the gestation length, whereas calf survival to weaning were affected of age of dam and year of birth.  Estimated heritability of  GL and CS were 0.68 ± 0.07  and 0.28 ± 0.09, respectively. With regards to genetic effect, estimated heritability of GL was considered higher (0.68), which means that GL information would be more effective as a selection criteria. Selection for shorter GL might be reduce calving problems with less impact on calf survival to weaning.